PENGARUH PERMODALAN, LIKUIDITAS, KUALITAS ASET TERHADAPPROFITABILITAS BANK UMUM SYARIAH YANG TERDAFTAR DI BANK INDONESIAÂ (PERIODE 2010 â€“ 2014) - PAMUNGKAS, LUKITO (Jurnal Akuntansi AKUNESA, 2016)
Bank as financial intermediary institutions in carrying out its business activities are classified into two categories, namely conventional banks and banks with Islamic principles. The importance of the function and role of Islamic banking in Indonesia, the Islamic banks need to improve its performance in order to create banks with Islamic principles of healthy and efficient. Profitability as a reference in measuring the profits to be so important to know whether the company has been running its business efficiently. This study examines the influence of capital, liquidity, and asset quality on the profitability of Islamic banks registered in Indonesian banks. In this study the profitability measured by using ROA.  The object of research in this research that Islamic banks registered in Bank Indonesia in 2010-2014, samples that can be used as many as 45 Islamic banks. Samples were taken by purposive sampling method where the sample selection on the characteristics of the population that is already known. Then analysis of the data obtained. Analysis of the data used in this study is the classical assumption test, multiple regression analysis, and hypothesis testing. To analyze the data using SPSS software tools.  From the results of hypothesis testing Capital Adequacy Ratio (CAR) have a effect on ROA in the Islamic Bank in Indonesia, Financing to Deposit Ratio (FDR) had no effect on ROA in the Islamic Bank in Indonesia, Non Performing Financing (NPF) negative effect on ROA in Islamic Bank in Indonesia.